Alpha-1 proteinase inhibitors for the treatment of alpha-1 antitrypsin deficiency: safety, tolerability, and patient outcomes - Chotirmall SH; Al-Alawi M; McEnery T; McElvaney NG (Dove Medical Press, 2015)
Sanjay H Chotirmall,1 Mazen Al-Alawi,2 Thomas McEnery,2 Noel G McElvaney2 1Lee Kong Chian School of Medicine, Nanyang Technological University, Singapore; 2Department of Respiratory Medicine, Beaumont Hospital, Dublin, Republic of Ireland Abstract: Alpha-1 antitrypsin (AAT) deficiency remains an underrecognized genetic disease with predominantly pulmonary and hepatic manifestations. AAT is derived primarily from hepatocytes; however, macrophages and neutrophils are secondary sources. As the natural physiological inhibitor of several proteases, most importantly neutrophil elastase (NE), it plays a key role in maintaining pulmonary protease–antiprotease balance. In deficient states, unrestrained NE activity promotes damage to the lung matrix, causing structural defects and impairing host defenses. The commonest form of AAT deficiency results in a mutated Z AAT that is abnormally folded, polymerized, and aggregated in the liver. Consequently, systemic levels are lower, resulting in diminished pulmonary concentrations. Hepatic disease occurs due to liver aggregation of the protein, while lung destruction ensues from unopposed protease-mediated damage. In this review, we will discuss AAT deficiency, its clinical manifestations, and augmentation therapy. We will address the safety and tolerability profiles of AAT replacement in the context of patient outcomes and cost-effectiveness and outline future directions for work in this field. Keywords: alpha-1, augmentation, deficiency, replacement, emphysema